(untitled) (Minerva, 2019)
Hermann the German († 1272/3), translator of the «School at Toledo», was only identified in 1819 thanks to A. Jourdain. In 1901 G. H. Luquet published a summary of studies to date, but one in which includes much wrong news or uncorroborated information. Until a short time ago, this incorrect information has been accepted as fact. Recently, W. F. Boggess made important contributions to knowledge of Hermann’s life and works. W. F. Boggess obtains his data from the prefaces and/or epilogues of Hermann’s five translations from Arabic to Latin, as well as the references that Roger Bacon, his contemporary, makes about (him) Hermann. However, the untimely death of the American researcher prevented him from investigating the possibility of obtaining new information in the Archives of the Diocese of Astorga, a town in the province of León where Hermann was bishop until his death.